The Russian Armed Forces “New Look” Reform (2008-2013) - Anak Agung Banyu Perwita, Naufal Ahaddin Caesarialdy , (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
Russia-Georgia relations had been declining since Georgia first voiced its intention for NATO membership in 2005 which later escalated into a war in 2008. Despite being victorious in the 2008 Russo-Georgian Five-Day War, the shortcomings of the Russian Armed Forces that were exposed during the war had led the country towards its “New Look” military reform announced months after the war. Many International Relations scholar draw a connection between the reform and Russia’s increasing assertiveness marked by the Crimean annexation and Russia’s involvement in Syria. This piece will then try to understand how Russian military performance in the 2008 war led to Russia’s most rigorous military reform, and more importantly, how did Russia implement its “New Look” reform during 2008 until 2013. Russia had underwent far reaching efforts and goals to transform the armed forces into combat-ready forces but had also faced challenges in modernizing its weaponry system, in increasing the quality and professionalism of its forces